Ascending Music: Meaning and Expression in the Chamber Music of Brian Cherney - Brook, Taylor (Intersections, 2017)
This article investigates the musical language of Brian Cherney, applying the idea of musical topics as a strategy for analyzing the extramusical content of his music. The idea of musical topics, traditionally applied to works from the classical era, is expanded with a collection of topics that are specific to Cherney’s work. Focusing on a set of chamber pieces from throughout Cherney’s compositional output beginning in the 1960s, this article focuses particularly on the topic of “ascending music,” tracing its musical and expressive meaning through these chamber works. The article concludes with a topic-based analysis of Gan Eden, a 1983 piece for violin and piano, providing an example of how topics coexist and interact within a single composition.